Bounded rationality, enactive problem solving, and the neuroscience of social interaction - Viale, Riccardo; Gallagher, Shaun; Gallese, Vittorio (Frontiers in Psychology, 2023)
We begin with a brief background history of Subjective Expected Utility (SEU) decision making, and some of its limitations. We then outline how Newell and Simon's approach to problem solving offers an alternative that reflects the concept of bounded cognition. We argue that this alternative fits well with the more recent research program of embodied cognition. The role of embodied cognition is fundamental in the pragmatic activity of problem solving. In regard to the bounded cognition involved in the problem-solving model, it is through the problem solver’s enactive interaction with environmental affordances, and especially social affordances that it is possible to construct the processes required for arriving at a solution.